Benefit Expectations and Continued Usage of Location-Based Applications for Location Intelligence - Koohikamali, Mehrdad; Mousavi, Reza; Peak, Daniel A.; Prybutok, Victor R. (Journal of Applied Business and Economics, 2020)
Location-based applications (LBA) are widely used for different purposes ranging from navigation to dating or gaming. Most LBAs ask users to provide access to location data. By disclosing location, users get customized services and businesses can enhance their services with location intelligence methods. This research builds a continuance usage and location disclosure model from the expectation-confirmation perspective. The effect of benefit expectations on usefulness and satisfaction is hypothesized. In addition, the positive effect of usefulness on satisfaction and continuance intention is postulated. After collecting survey data from main LBA users, the results of the analysis support the proposed model.